The IFN-γ-inducible GTPase, Irga6, protects mice against Toxoplasma gondii but not against Plasmodium berghei and some other intracellular pathogens. - Oliver Liesenfeld (Public Library of Science (PLoS), 2011)
Clearance of infection with intracellular pathogens in mice involves interferon-regulated GTPases of the IRG protein family. Experiments with mice genetically deficient in members of this family such as Irgm1(LRG-47), Irgm3(IGTP), and Irgd(IRG-47) has revealed a critical role in microbial clearance, especially for Toxoplasma gondii. The in vivo role of another member of this family, Irga6 (IIGP, IIGP1) has been studied in less detail. We investigated the susceptibility of two independently generated mouse strains deficient in Irga6 to in vivo infection with T. gondii, Mycobacterium tuberculosis, Leishmania mexicana, L. major, Listeria monocytogenes, Anaplasma phagocytophilum and Plasmodium berghei. Compared with wild-type mice, mice deficient in Irga6 showed increased susceptibility to oral and intraperitoneal infection with T. gondii but not to infection with the other organisms. Surprisingly, infection of Irga6-deficient mice with the related apicomplexan parasite, P. berghei, did not result in increased replication in the liver stage and no Irga6 (or any other IRG protein) was detected at the parasitophorous vacuole membrane in IFN-γ-induced wild-type cells infected with P. berghei in vitro. Susceptibility to infection with T. gondii was associated with increased mortality and reduced time to death, increased numbers of inflammatory foci in the brains and elevated parasite loads in brains of infected Irga6-deficient mice. In vitro, Irga6-deficient macrophages and fibroblasts stimulated with IFN-γ were defective in controlling parasite replication. Taken together, our results implicate Irga6 in the control of infection with T. gondii and further highlight the importance of the IRG system for resistance to this pathogen.